Africa's Pulse, No. 23, April 2021 : An Analysis of Issues Shaping Africa’s Economic Future - Zeufack, Albert G. (World Bank, Washington, DC, 2021)
The economic impact of the COVID-19 pandemic in Sub-Saharan Africa has been severe; however, countries are weathering the storm so far. Real GDP is estimated to contract by 2.0 percent in 2020—close to the lower bound of the forecast range in April 2020, and less than the contraction in advanced economies and other emerging markets and developing economies, excluding China. Available data from the second half of 2020 point to rebound in economic activity that explain why the contraction in the region was in the lower bound of the forecasts. It reflected a slower spread of the virus and lower COVID-19-related mortality in the region, strong agricultural growth, and a faster-than-expected recovery in commodity prices. Economic activity in the region is expected to rise to a range between2.3 and 3.4 percent in 2021, depending on the policy measures adopted by countries and the international community. However, prospects for a slow vaccine rollout, the resurgence of pandemic, and limited scope for additional fiscal support, could hold back the recovery in the region. Policies to support the economy in the near term should be complemented by structural reforms that encourage sustained investment, create jobs and enhance competitiveness. Reducing the countries’ debt burden will release resources for public investment, in areas such as education, health, and infrastructure. Investments in human capital will help lower the risk of long-lasting damage from the pandemic which may become apparent over the longer term, and can enhance competitiveness and productivity. The next twelve months will be a critical period for leveraging the African Continental Free Trade Area in order to deepen African countries’ integration into regional and global value chains. Finally, reforms that address digital infrastructure gaps and make the digital economy more inclusive –ensuring affordability but also building skills for all segments of society, are critical to improve connectivity, boost digital technology adoption, and generate more and better jobs for men and women.